Effect of Soil Application of Stabilized Ortho Silicic Acid Based Granules on Growth and Yield of Rice (Oryza sativa L.). Issue 4 (21st February 2023) - Abayisenga, Jean Claude; Mbaraka, Saidi Rumanzi; Nkurunziza, Christian; Shema, Maurice Jules; Murenzi, Fidele; Rucamumihigo, Francois Xavier; Habimana, Sylvestre; Persson Hovmalm, Helena; Neeru, Jain; Rushemuka, Pascal; Cyamweshi, Athanase Rusanganwa; Ndikumana, Innocent
ABSTRACT: Rice ( Oryza sativa L.) is one of the most important cereal crops in Rwanda. Present study was aimed assessed the effect of stabilized ortho silicic acid (OSA) based granules on growth and yield of rice. Field experiments were conducted at Rwagitima, Gatsibo district in the Eastern province of Rwanda during two wet seasons in 2019, the first season was between February and May and the second one was from September to December. Two levels of recommended fertilizer doses (RDF; i.e., 200 kg ha −1 NPK as a basal fertilizer and 100 kg ha −1 urea as a top dressing fertilizer) were applied solely and along with different doses (10, 15 and 20 kg ha −1 ) of OSA based granules. The treatments were: T1 (100% RDF), T2 (75% RDF), T3 (T1 +10 kgha −1 OSA), T4 (T1 +15 kgha −1 OSA), T5 (T1 +20 kgha −1 OSA), T6 (T2 +10 kgha −1 OSA), T7 (T2 +15 kgha −1 OSA) and T8 (T2 +20 kgha −1 OSA). Experiments were laid in a randomized complete block design (RCBD) with three replications. Results showed that the application of 100% RDF +20 kg ha −1 of OSA granules increased plant height (99.80 cm), tiller number (361) and root length (15.7 cm). Furthermore, yield increments of 28.4% and 19.9% for the first and second seasons, respectively, were obtained in treatments where 100% RDF +20 kgha −1 of OSA granules were applied. The rice yield in the treatment 75% RDF +20 kg/ha Silixol OSA granules was higher than that recorded with 100% RDF only. This indicates that use of Silixol OSA granules can result in 25% saving of fertilizer (NPK and urea) without compromising the yield. Conclusively, Silixol OSA granules offers good potential for yield increment of rice in Rwanda and, can minimize fertilizer use by 25%.